Prva vstavitev biološke aortne zaklopke preko femoralne arterije v Sloveniji - Bunc, Matjaž (Zdravniški vestnik, 2010)
Calcified aortic stenosis is the most frequent valvular heart disease in the Western world. It is a progressive, degenerative, atheroscleroticlike process that involves the aortic valve with increasing prevalence as the population ages. Surgical aortic valve replacement is the treatment of choice for patients with severe, symptomatic aortic stenosis, but it has limitations in old patients with high perioperative risk and in patients with comorbidities. A new method of percutanous aortic valve implantation has been developed recently. It is indicated insymptomatic patients with high perioperative risk.Case report: A case of a 83-year-old female patient with severe, symptomatic aortic valve stenosis and a high haemorrhagic risk due to vascularectatic changes after surgery for gastric carcinoid tumor is reported.She was refused for surgical aortic valve replacement. Transfemoral implantation of Edwards SAPIEN aortic valve was indicated. On the day after implantation the patient stood up; she improved clinically as well as objectively. Conclusions: Our case shows that there are additional therapeuticoptions for high-risk patients with severe aortic stenosis. Transfemoral aortic valve implantation is a procedure that does not require anaesthesia and thoracotomy. The implantation requires teamwork involving interventional cardiologist, cardio-vascular surgeon and anaesthesiologist. The real clinical value of the method is yet to be established as a result of ongoing clinical trials and in cooperation between interventional cardiologists and cardiac surgeons.
Keywords: Aged; Aortic Valve Stenosis; Aortna zaklopka, stenoza; Catheters, Indwelling; Femoral Artery; Femoralna arterija; heart; Heart Valve Prolapse; Katetri, vstavljanje; srce; Srčna zaklopka, prolaps; srčne bolezni; srčne zaklopke; Starostniki; stenoza; Surgery; therapy; Treatment Outcome; zdravljenje; Zdravljenje, izid